2013
DOI: 10.1101/gad.215137.113
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional elongation checkpoint control in development and disease

Abstract: Transcriptional elongation control by RNA polymerase II and its associated factors has taken center stage as a process essential for the regulation of gene expression throughout development. In this review, we analyze recent findings on the identification of factors functioning in the regulation of the transcriptional elongation checkpoint control (TECC) stage of gene expression and how the factors' misregulation is associated with disease pathogenesis, including cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 95 publications
(140 reference statements)
2
54
1
Order By: Relevance
“…Given the fact that the misregulation of the elongation stage of transcription has been associated with human diseases, including cancer (Smith and Shilatifard 2013), the use of TPL for the in vivo study of transcriptional elongation control should be very informative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the fact that the misregulation of the elongation stage of transcription has been associated with human diseases, including cancer (Smith and Shilatifard 2013), the use of TPL for the in vivo study of transcriptional elongation control should be very informative.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter-proximal paused Pol II is prevalent in metazoans, particularly at genes related to developmental and environmental pathways (Core and Lis 2008;Adelman and Lis 2012;Smith and Shilatifard 2013). In Drosophila, it has been shown that minimal promoter elements with paused Pol II are sufficient to mediate a synchronous pattern of gene expression during development (Lagha et al 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(D) Therapeutic targeting of MLL translocated leukemia. MLL chimeras recruit SEC and/or DotCom to MLL target genes, which leads to their aberrant activation through misregulation of the transcriptional elongation checkpoint (Smith and Shilatifard 2013). Multiple therapeutic strategies have been developed to target different steps required for the activation of MLL chimera target genes in leukemia: MI503 blocks the association of Menin with MLL, potentially affecting recruitment of the MLL chimera to chromatin (indicated by a question mark); flavopiridol (FP) inhibits the kinase activity of SEC subunit P-TEFb; and EPZ-5676 is a small molecule blocking the enzymatic activity of DOT1L.…”
Section: Mll In Normal Hematopoiesis and In The Transcriptional Elongmentioning
confidence: 99%
“…2,48 Characterization of the structure and function of this novel transcription elongation checkpoint will provide new insights into regulation of gene expression at the level of transcription elongation and how this might be misregulated in human disease.…”
Section: Future Prospectsmentioning
confidence: 99%